2014
DOI: 10.1111/vec.12144
|View full text |Cite
|
Sign up to set email alerts
|

Partnership on Rotational ViscoElastic Test Standardization (PROVETS): Evidence‐based guidelines on rotational viscoelastic assays in veterinary medicine

Abstract: Evidence-based guidelines for the performance of thromboelastography in companion animals were generated through this process. Some of these guidelines are well supported while others will benefit from additional evidence. Many knowledge gaps were identified and future work should be directed to address these gaps and to objectively evaluate the impact of these guidelines on assay comparability within and between centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 144 publications
(231 reference statements)
4
138
0
3
Order By: Relevance
“…A model‐based scoring system was developed in veterinary medicine, but the application of this scoring system was not possible in this study, because it used reference intervals for tests performed at 1 specific laboratory. Finally, no discard tube was used to collect the blood samples, unlike the recommended standard . It is possible that this method of blood collection led to preanalytical bias.…”
Section: Discussionmentioning
confidence: 99%
“…A model‐based scoring system was developed in veterinary medicine, but the application of this scoring system was not possible in this study, because it used reference intervals for tests performed at 1 specific laboratory. Finally, no discard tube was used to collect the blood samples, unlike the recommended standard . It is possible that this method of blood collection led to preanalytical bias.…”
Section: Discussionmentioning
confidence: 99%
“…The present study employed a nonhemorrhagic model, and hypercoagulability was not a finding, suggesting the results are still relevant. Finally, half of the TEM samples were run 60 minutes after collection, instead of the recommended 30 minutes . Studies have shown that samples appear to become more hypercoagulable with time .…”
Section: Discussionmentioning
confidence: 99%
“…Practices using point‐of‐care viscoelastic devices will need to use established veterinary clinical pathology guidelines to determine reference intervals (Goggs et al . ).…”
Section: Laboratory Assessment Of Fibrinolysismentioning
confidence: 97%